Online Learning Perception and Nursing Student Learning Motivation During the Covid-19 Pandemic - Lembunai Tat Alberta; Dwi Adji Norontoko; Irfany Nurul Hamid (Humanistic Network for Science and Technology (HNST), 2022)
Countries in the world including Indonesia are being hit by the health problems of the corona virus (Covid-19) pandemic. The government continues to carry out various handling and prevention efforts, especially in controlling the spread of COVID-19 in the community, including students who carry out learning activities on campus. One of the efforts made is to implement policies regarding the learning process through online learning. Online learning methods cause different perceptions among students and this has an impact on several things including student learning motivation. The study was conducted to analyze the relationship between students' perceptions of online learning methods on student motivation in nursing at the Sutomo campus, Surabaya. The research method was observational analytic with a cross-sectional approach. Online data collection using Google Form, data analysis using Spearman's rho statistical test. The results showed that there was a significant relationship between students' perceptions of online learning and students' learning motivation (p = 0.00). It is recommended to increase student learning motivation through improving facilities, infrastructure, facilities and learning methods as well as positive perceptions of online learning. Keywords: online learning; nursing students; perceptions; motivation